Identification of a de novo Mutation in TMEM106B in a Saudi Child Causes Hypomyelination Leukodystrophy - Alotaibi, Lena; Alqasmi, Amal (Global Medical Genetics, 2023)
Hypomyelinating leukodystrophies are one of the white matter disorders caused by a lack of myelin deposition in the central nervous system (CNS). Here, we report the first case of hypomyelinating leukodystrophy in the Middle East and Saudi Arabia. This condition is caused by a mutation in the TMEM106B gene (HLD16; MIM 617964). Hypotonia, congenital nystagmus, delayed motor development, and delayed speech are the main clinical manifestations. The affected patient has mild pyramidal syndrome, a mild intellectual disability, ataxic gait, hyperreflexia, intention tremor, dysmetria, and other motor difficulties. Findings from neuroimaging reveal severe, ongoing, and diffuse hypomyelination identified via the whole exome sequencing, a harmful missense mutation in the TMEM106B gene that is heterozygous. The patient is the offspring of two unrelated persons. The protein's cytoplasmic domain contains a variation that is located in highly conserved residues. In an oligodendroglial cell line, the mutant protein significantly lowered the mRNA production of important myelin genes, decreased branching, and increased cell mortality. TMEM106B is abundantly expressed in neurons and oligodendrocytes in the CNS and is localized in the late endosome and lysosome compartments. TMEM106B levels can be controlled at the transcriptional level through chromatin modification, at the mRNA level through miRNAs, and at the protein level through lysosomal functions. Our findings reveal a novel role of zinc homeostasis in oligodendrocyte development and myelin production and show that variations in TMEM163 induce hypomyelination leukodystrophy.
Keywords: TMEM106; Exome; hypomyelinating leukodystrophies; mutation